1997
DOI: 10.1007/s004140050033
|View full text |Cite
|
Sign up to set email alerts
|

Sequence polymorphism at the tetranucleotide repeat of the human beta-actin related pseudogene H-beta-Ac-psi-2 (ACTBP2) locus

Abstract: The tetranucleotide repeat polymorphism in the human beta-actin related pseudogene H-beta-Ac-psi-2 (ACTBP2) locus has become a widely used short tandem repeat (STR) system in paternity testing and human identification. The discrimination index of this locus has been reported to be as high as 99.65%. To study the overall variability of this locus, 222 alleles were sequenced in our laboratory. Here, we report the sequences of the 102 different alleles observed. In addition to the length polymorphism, up to ten d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 7 publications
0
29
0
Order By: Relevance
“…Alleles showing the same electrophoretic mobility under denaturing conditions, but different positions in a non-denaturing gel system are marked by an asterisk. The "consensus nomenclature" introduced by the ACTBP2 working group of the German Society of Legal Medicine and published by Rolf et al (1997) …”
Section: Resultsmentioning
confidence: 99%
“…Alleles showing the same electrophoretic mobility under denaturing conditions, but different positions in a non-denaturing gel system are marked by an asterisk. The "consensus nomenclature" introduced by the ACTBP2 working group of the German Society of Legal Medicine and published by Rolf et al (1997) …”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that more than 100 alleles have been observed due to sequence variations (Rolf et al 1997). But this high degree of polymorphism leads to considerable problems for the designation of alleles.…”
Section: Resultsmentioning
confidence: 99%
“…Some alleles larger than 317 bp (i.e. 33.2) have been found which contain a second hexamer motif (Rolf et al 1997) and these are designated by a whole number (e.g. 33) because the two incomplete motifs can be considered as one complete unit.…”
Section: Resultsmentioning
confidence: 99%
“…The first collaborative EDNAP effort in 1994 showed general agreement on the results obtained from simple STR loci but diversity with the results achieved in the analysis of high microvariation microsatellites, such as HUMACTBP2 [17]. Nevertheless, for a high percentage of forensic DNA laboratories in Europe (30%) the human beta-actin-related pseudogene is still the marker of first choice when the processing of large numbers of samples is required [18J, providing an alternative to common multiplex STR systems [19-221. However, allelic ladders already constructed for the ACTBP2 contain only 21-25 length variants [13,23,241, whereas at least 82 sequence variants have also been reported [25]. Consequently, methods distinguishing alleles solely by size have the potential for misinterpretation and therefore are not sufficient in ACTBP2 typing.…”
Section: Discussionmentioning
confidence: 99%